2020
DOI: 10.1021/acs.iecr.0c02800
|View full text |Cite
|
Sign up to set email alerts
|

Biotemplated Fabrication of 3D Hierarchically Porous MgAl-LDH/CF Composites with Effective Adsorption of Organic Dyes from Wastewater

Abstract: The serious pollution of water resources has brought great challenges to human existence; it is urgent to develop adsorbents for removing toxic dyes from wastewater. In this work, we synthesized hierarchically porous MgAl-layered double hydroxide (LDH)/carbon fiber (CF) composites with excellent adsorption of Congo red (CR) by combining the biotemplating and hydrothermal method. The effects of various Mg/Al molar ratios on the X-ray powder diffraction (XRD), scanning electron microscopy (SEM), Brunauer− Emmett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 56 publications
(92 reference statements)
1
14
0
Order By: Relevance
“…coli were best fitted to Freundlich linear and nonlinear models shown in Figure a–f, which corresponded to the higher R 2 values of the Freundlich model than the Langmuir model shown in Table . Literature review shows that other studies also found the same results as this study, that is, the results of the adsorption linear model agreed to those of the nonlinear model, and the equilibrium isotherm parameters of both linear and nonlinear models had close values. As a result, both linear and nonlinear adsorption models are necessary to plot and calculate all isotherm parameters for confirming which adsorption model is the best-fit model to the actual experiment values to avoid errors. , …”
Section: Resultssupporting
confidence: 80%
“…coli were best fitted to Freundlich linear and nonlinear models shown in Figure a–f, which corresponded to the higher R 2 values of the Freundlich model than the Langmuir model shown in Table . Literature review shows that other studies also found the same results as this study, that is, the results of the adsorption linear model agreed to those of the nonlinear model, and the equilibrium isotherm parameters of both linear and nonlinear models had close values. As a result, both linear and nonlinear adsorption models are necessary to plot and calculate all isotherm parameters for confirming which adsorption model is the best-fit model to the actual experiment values to avoid errors. , …”
Section: Resultssupporting
confidence: 80%
“…39 On comparing the linear and non-linear adsorption isotherm models, their results were found to have close adsorption parameters, which represented the agreement results of linear and non-linear models similarly to other studies. [74][75][76][77] As a result, the plotting of the linear and non-linear adsorption isotherm models is necessary to avoid data mistranslation. 78,79…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…In SPE, the analyte-containing solvent interacts with a sorbent material that has a high affinity for the analyte that needs to be isolated [47]. Due to the internal layered organization and porous structure of natural materials, biotemplating has been of great interest to develop adsorbents with improved adsorption capacity and to reduce the limitations of current commercial adsorbents, including high cost, pH instability and a difficult synthesis process [46,48]. These adsorbents have been used for different purposes.…”
Section: Applications 21 Adsorbentsmentioning
confidence: 99%
“…The adsorbents showed high adsorption rates (86-98%) when they were applied to mineral water and could remove PAHs from tap water completely, which suggests that this templated-adsorbent might be useful for removing those pollutants from food wastewaters [49]. In another study [48], researchers developed a 3D porous-structure nanosheet of MgAl-layered double hydroxide anchored on carbon fibers using cotton as the template to remove organic dyes from water. Congo red was used as a model water pollutant to demonstrate the adsorption capacity of the material.…”
Section: Applications 21 Adsorbentsmentioning
confidence: 99%